Biodegradable pH-responsive hydrogels for controlled dual-drug release - Liang Xu; Linzi Qiu; Yang Sheng; Yixin Sun; Linhong Deng; Xinqing Li; Mark Bradley; Rong Zhang (2017)
pH-Responsive biodegradable hydrogels based on NIPAM/AA and a PLLA/PEG macro-crosslinker demonstrated pH mediated differential release of doxorubicin and tetracycline.